Enhanced photocatalytic activity, transport properties and electronic structure of Mn doped GdFeO3 synthesized using the sol–gel process. Issue 30 (22nd July 2021) - Maity, Ritwik; Dutta, Alo; Halder, Saswata; Shannigrahi, Santiranjan; Mandal, Kalyan; Sinha, T. P.
Abstract : Mn doping reduced the band gap to 1.72 eV from 2.18 eV which is confirmed from electronic structure calculations. GdFe0.7 Mn0.3 O3 exhibits 99% Rh-B degradation at 25 minutes. The multiple oxidation states of Fe and Mn enhances the conductivity and Mn doping reduces the barrier width which facilitates the charge transfer process. Abstract : In this work we have synthesized Mn doped GdFeO3 nano-particles using a green and facile sol gel method and studied their photocatalytic, optical, vibrational and electrical properties. The Rietveld refinement of the XRD profiles suggests that all the materials have an orthorhombic Pbnm crystal structure. The transmission electron microscope (TEM) images show the decrease of the average particle size from 140 to 80 nm with the Mn concentration. The high crystallinity of the synthesized particles is confirmed from the HR-TEM images. Raman spectrum is employed to investigate the phonon modes of the materials. The optical band gap of the materials is obtained from the UV-vis reflectance spectroscopy (DRS) using Tauc relation which indicates the reduction of the band gap from 2.18 to 1.72 eV with Mn-doping. The photocatalytic activity of the materials is studied by the photocatalytic degradation of rhodamine B (Rh-B) in aqueous solution under visible light illumination. The substitution of Mn at the Fe site introduces an extra electronic state between the conduction band and the valence band which reduces the electronic band gap and enhances the Rh-B degradation efficiency. A 30% Mn doping at the Fe site (GFMO3) provides an optimum space charge width which assists to attain the maximum rate of degradation of the Rh-B dye. The doping of Mn 3+ reduces the photogenerated electron and hole recombination rate and hence more charge carriers take part in the redox reaction which facilitates the photo-catalytic efficiency in GFMO3. The degradation rate enhances by a factor of 2.5 for GFMO3 as compared to pure GdFeO3 . The highest photocurrent density of 1.31 μA cm −2 of GFMO3 with respect to other materials promotes the separation and transfer of the photo generated charge carriers. The possible photocatalytic mechanism of the Mn doped GdFeO3 is also critically discussed. Alternating current impedance spectroscopy is used to study the electrical properties of the synthesized materials. The increase in the conductivity with the Mn concentration is explained on the basis of the band gap reduction and this is consistent with the Smit and Wijn theory. Magnetic measurement is performed to measure the magnetization strength which is useful to separate the photocatalyst by simply using a magnet. The temperature dependent magnetization measurement suggests the anti-ferromagnetic (AFM) behaviour of the studied materials with the decrease of Néel temperature (TN) with Mn concentration. The XPS study reveals the presence of multiple oxidation states of Fe(2+/3+) and Mn(4+/3+) in these materials which facilitates the conductivity as well as the oxidation/reduction efficiency at the surface of the catalyst. The band gap reduction and its effect on the enhancement of the photocatalytic degradation efficiency with Mn doping are also discussed from the density of states calculations. Thus, this study describes a promising approach for the organic pollutant degradation by designing an efficient and stable perovskite photocatalyst.